2004
DOI: 10.1007/s00125-004-1356-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of orally active poly(ADP-ribose) polymerase inhibitor in streptozotocin-diabetic rat model of early peripheral neuropathy

Abstract: Aims/hypothesis. Poly(ADP-ribose) polymerase activation depletes NAD + and high-energy phosphates, activates protein kinase C, and affects gene expression in various tissues. This study was designed to characterise the effects of the potent, orally active poly(ADP-ribose) polymerase inhibitor PJ34 in the Wistar rat model of early diabetic neuropathy. Methods. Control and streptozotocin-diabetic rats were maintained with or without PJ34 treatment (30 mg·kg −1 ·day −1 ) for two weeks, after two weeks without tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In diabetic rats, activity of 6-phosphofructokinase is reduced in nerve (35), and activity of hexokinase, the first rate-limiting step in glycolysis, is reduced in DRG (36). Diminished activity of glycolytic pathway enzymes may combine to reduce delivery of pyruvate and other glucose metabolism-dependent products to the tricarboxylic acid pathway (3234,37), and it has been shown that pool sizes of products of glycolysis, such as pyruvate, are either unchanged or reduced in diabetes (33,38). It therefore appears that rates of electron donation to the electron transport chain are suboptimal in adult diabetic rats and may predispose to lower rates of mitochondrial respiratory chain activity and oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic rats, activity of 6-phosphofructokinase is reduced in nerve (35), and activity of hexokinase, the first rate-limiting step in glycolysis, is reduced in DRG (36). Diminished activity of glycolytic pathway enzymes may combine to reduce delivery of pyruvate and other glucose metabolism-dependent products to the tricarboxylic acid pathway (3234,37), and it has been shown that pool sizes of products of glycolysis, such as pyruvate, are either unchanged or reduced in diabetes (33,38). It therefore appears that rates of electron donation to the electron transport chain are suboptimal in adult diabetic rats and may predispose to lower rates of mitochondrial respiratory chain activity and oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, NF- κ B activation has been shown to increase Cu/Zn -superoxide dismutase (SOD) expression and MnSOD levels after H 2 O 2 and amyloid beta (A β ) treatment, protecting against oxidative stress and apoptosis in PC12 and NT2 cells, respectively [77, 78]. Alternatively, PI-3K/Akt activation may promote neuronal and glial antioxidant defences by stimulation of the Nrf-2/antioxidant responsive element (ARE) [79]. …”
Section: Neuronal Ir/igf-1r-mediated Signaling Pathwaysmentioning
confidence: 99%
“…SIRT1-mediated regulation of PGC-1α activity may play a major role in the metabolic adaptations to energy metabolism in different tissues (Canto and Auwerx, 2010). Recent work shows high glucose can down-regulate SIRT1 expression in endothelial cells (Balestrieri et al, 2008) and the diabetic state lowers the NAD + /NADH ratio in retina and nerve (Ido et al, 2010; Li et al, 2004; Oates, 2008; Obrosova et al, 2006). …”
Section: Ampk/sirt/pgc-1α Pathway In Neuronsmentioning
confidence: 99%